Mr. and Mrs. Roy W. Davidson (Raton Range Raton, New Mexico, 1987)
Newspaper Article on the 50th Anniversary of Mr. and Mrs Roy W. Davidson.
Master list item #: 62
File location is in the Raton File Cabinet
Keywords: Davidson, Roy W; Davidson, Sue Catherine; Erwin, Jane; Woodward, Betty; Groth, Edward; Groth, Sue; Groth, Patty; Groth, David; Groth, Valerie; Overpeck, James G; Overpeck, Mary; Overpeck, Charles; Overpeck, George; Overpeck Dorothy; Davidson, John P; Davidson, Robbie; Davidson, Joshua; Davidson, Paige; Jones, Larry; Jones, Judy; First United Methodist Church; Local History; Biography; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico; Las, Cruces, New Mexico; Great Falls, Virginia; Albuquerque, New Mexico